2016
DOI: 10.3414/me14-01-0071
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cognitive Impairment Compatible with Early Diagnosis of Alzheimer’s Disease

Abstract: Our method is able to analyse LSCD in a wide set of semantic categories throughout the progression of CI, being a valuable first screening method in AD diagnosis in its early stages. Because of its low cost, it can be used for routine clinical evaluations or screenings to detect AD in its early stages. Besides, due to its knowledge-based structure, it can be easily extended to provide an explanation of the diagnosis and to the study of other neurodegenerative diseases. Further, this is a key advantage of BNs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Our results show that we have a possible indicator of early AD, due to areas of 0.89 and 0.7 obtained, which is considered acceptable for an ROC curve. The results are also comparable to those obtained by Guerrero et al ( 2016 ) with 91 and 94% precision for detecting AD, while our study obtained a precision of 88%. These studies can be compared with early indicators or screening of the likely onset of AD.…”
Section: Conclusion and Further Research Worksupporting
confidence: 92%
“…Our results show that we have a possible indicator of early AD, due to areas of 0.89 and 0.7 obtained, which is considered acceptable for an ROC curve. The results are also comparable to those obtained by Guerrero et al ( 2016 ) with 91 and 94% precision for detecting AD, while our study obtained a precision of 88%. These studies can be compared with early indicators or screening of the likely onset of AD.…”
Section: Conclusion and Further Research Worksupporting
confidence: 92%
“…From this, we concluded that for the linguistic features considered, there is no need to separate participants' descriptions into living and non-living categories. Guerrero et al (2016) reported an accuracy of 91% (see Table 1) and an AUC of 0.9636. They used a Bayesian Network fed with manuallyextracted attributes and incorporated participants' socio-demographic information as a priori deterministic inputs.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The cohort used by Guerrero et al (2016) in their study includes a total of 69 participants (30 controls and 39 AD patients previously diagnosed by neurologists) aged between 55 and 95 years old. For each participant, Peraita and Grasso recorded free oral descriptions of six common objects (referred in their work as "semantic categories"): dog, apple, pine (living things), car, trousers and chair (non-living things).…”
Section: Corpusmentioning
confidence: 99%
See 1 more Smart Citation
“…Because its procedures of reasoning and expression can be easily understood and accepted by both therapists and patients, unlike the black box of other traditional algorithms, it is also able to present uncertainties and causalities, which are both important in the medical domain [12]. Several studies have examined the performance of BN by developing mathematical models for diagnosing different diseases, including breast cancer [13], lung cancer [14], and Alzheimer disease [12,15]. These experimental results showed that all models of these disease diagnoses provided accuracy of at least 80%, and their network structures could be easily understood.…”
Section: Introductionmentioning
confidence: 99%